Antenatal Medical Therapies to Improve Lung Development in Congenital Diaphragmatic Hernia - Kashyap, Aidan; DeKoninck, Philip; Crossley, Kelly; Thio, Marta; Polglase, Graeme; Russo, Francesca Maria; Deprest, Jan; Hooper, Stuart; Hodges, Ryan (American Journal of Perinatology, 2018)
Congenital diaphragmatic hernia (CDH) is a birth defect characterized by failed closure of the diaphragm, allowing abdominal viscera to herniate into the thoracic cavity and subsequently impair pulmonary and vascular development. Despite improving standardized postnatal management, there remains a population of severe CDH for whom postnatal care falls short. In these severe cases, antenatal surgical intervention (fetoscopic endoluminal tracheal occlusion [FETO]) may improve survival; however, FETO increases the risk of preterm delivery, is not widely offered, and still fails in half of cases. Antenatal medical therapies that stimulate antenatal pulmonary development are therefore interesting alternatives. By presenting the animal research underpinning novel antenatal medical therapies for CDH, and considering the applications of these therapies to clinical practice, this review will explore the future of antenatal CDH management with a focus on the phosphodiesterase-5 inhibitor sildenafil.
Keywords: congenital diaphragmatic hernia; antenatal therapy; fetal; sildenafil; pulmonary hypertension of the newborn; pulmonary hypoplasia